HUBUNGAN ANTARA PENGUASAAN DIKSI DAN KREATIVITAS VERBAL DENGAN KETERAMPILAN MENULIS PUISI PADA SISWA SEKOLAH MENENGAH PERTAMA - Rohmah, Kristiana Rizqi; Setiawan, Budhi; Sumarwati, Sumarwati (Jurnal S2 Pendidikan Bahasa Indonesia, 2016)
Skill writing poetry in a student VIII SMPN district Magetan relating to two factors namely mastery diction and creativity verbal. This research have aims test the whereabout of: (1) the relationship between mastery diction and skill wrote poems; (2) the relationship between creativity verbal with skill wrote poems; and (3) the relationship between mastery diction and creativity verbal in bersama-sama with skill writing poetry. Research method used in this research is survey with correlational study. Sample consists of four public schools, namely: SMPN 1 Maospati as schools that have high performance, state the SMPN 1 Â Barat as having school achievement was, state SMPN 2 Maospati as schools that have low achievement and SMPN 2 Barat class test as an instrument with the total sample 20 students taken with clusters of random sampling. Based on the results of research findings can be concluded as follows: (1) there was a correlation a significant positive between mastery diction and skills wrote poems with the results of regression simple of Å¶ = 39.99 + 1.16X1, correlation of 0.90 and results of the contribution of 81 %; (2) there was a correlation a significant positive between creativity verbal with skill wrote poems with the results of regression simple of Å¶Â = 19.27 + 0.52X2, correlation of by 0.80 and results of the contribution at 64 %; and (3) there was a correlation a significant positive between mastery diction and creativity verbal together with skill wrote poems with the results of regression double of Å¶ = 27.19 + 0.86X1 + 0.21X2, correlation of 0.97 and results of the contribution of 94.09 %.